Boron Trifluoride‐Mediated Trifluoromethylthiolation of N‐Acyliminiums. Issue 14 (15th May 2018) - Maury, Julien; Force, Guillaume; Darses, Benjamin; Lebœuf, David
Abstract: Herein, we describe a hitherto unprecedented trifluoromethylthiolation of N ‐acyliminiums promoted by boron trifluoride etherate to enable a convenient access to various α‐amino trifluoromethylthiolate derivatives in good yields. The reaction proceeds under mild conditions, relying on copper(I) trifluoromethylthiolate as a nucleophilic partner. Abstract :